Analysis of The Availability of Braille Collections at The Public Library of Deli Serdang Regency Based on The Needs of The Visually Impaired - Dwi Ayu Wulandari; Abdi Mubarak Syam (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
Libraries have an important role in finding information for all groups without exception, including the visually impaired. The availability and utilization of braille collections in public libraries still faces various challenges due to the lack of braille collections and lack of facilities for the visually impaired. The availability of braille collections in public libraries in Deli Serdang Regency is not professional with the number and needs of the visually impaired community. This condition causes the phenomenon of unequal access to information for the visually impaired. This study aims to analyze the availability of braille collections at the Deli Serdang Public Library and their relevance to the needs of visually impaired users. Library and their relevance to the needs of visually impaired users. A descriptive qualitative method was used through interviews, observations, and literature review. The results show that only 76 braille items are available, with limited variety to meet users’ interests. There is no specific acquisition policy, and librarians lack inclusive service training. However, librarians play an active role in assisting and identifying user needs through a personal approach.